2017
DOI: 10.3892/ol.2017.6520
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of ampelopsin from Ampelopsis megalophylla induces apoptosis in HeLa cells

Abstract: Ampelopsin (AMP) is an active ingredient of flavonoid compounds that is extracted from Ampelopsis megalophylla Diels et Gilg. The present study aimed at investigating the antitumor activities of AMP and the possible underlying molecular mechanisms in HeLa cells. A total of three types of tumor cell were selected to screen antitumor activities for AMP using the MTT assay. Flow cytometry was used to analyze the cell apoptotic proportion and the cell cycle. Rhodamine 123 staining was used to determine changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This suggests that eriodictyol might induce DNA replication damage in glioma cells (Bailon-Moscoso et al, 2017). Similar to our findings, other anti-cancer flavonoid compounds, such as ampelopsin, quercetin, and baicalein also arrest the cell cycle at the S phase (Mu et al, 2016;Srivastava et al, 2016;Cheng et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that eriodictyol might induce DNA replication damage in glioma cells (Bailon-Moscoso et al, 2017). Similar to our findings, other anti-cancer flavonoid compounds, such as ampelopsin, quercetin, and baicalein also arrest the cell cycle at the S phase (Mu et al, 2016;Srivastava et al, 2016;Cheng et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…The suppressing effect of DHM on the MDA-MB-231 breast cancer cell line was reported through ROS generation, ER stress pathway, and inhibition of mTOR [28,31]. DHM treatment dose-dependently inhibited the growth of HeLa cells by inducing apoptosis through activation of caspases 9 and 3 and increasing the ratio of Bax protein to Bcl-2 [44]. In A549 human adenocarcinoma lung epithelial cells, DHM decreased XIAP and survivin expression levels and cleaved poly(ADP-ribose) polymerase.…”
Section: Dihydromyricetin Exerts Its Chemopreventive Potential Againsmentioning
confidence: 99%
“…DHM effectively showed anticancer activity in a variety of cancers such as breast cancer, hepatocellular carcinoma, melanoma, ovarian cancer, lung cancer, cervical carcinoma, glioma, and osteosarcoma [32,33,[42][43][44][45][46]. Among the treatments for different cancer cells, DHM has a broad dosage from 1 to 1000 μM with a duration from 6 to 72 h, presenting cell proliferation inhibition and apoptosis-inducing effects ( Table 1).…”
Section: Dihydromyricetin Exerts Its Chemopreventive Potential Againsmentioning
confidence: 99%
“…Its tender leaves and stems are commonly used as a herbal tea and to prevent hypertension, particularly in the west of Hubei province (14). Pharmacological research has suggested that A. megalophylla has hypertensive, antiinflammatory, antiviral, antitumor, hyperglycemic, antimicrobial, hepatoprotective, neuroprotective, and antioxidant activities (15)(16)(17). Notably, its principal effective components are flavonoids and total flavone extract (TFE), which contains compounds, such as ampelopsin, myricetin and myricitrin.…”
Section: Introductionmentioning
confidence: 99%